Honeypot: Nástroj v boji proti malware - Karger, David (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2018)
Tato bakalářská práce se zabývá nasazením honeypotu pro boj s malwarem. Cílem bylo nastudování problematiky honeypotů a jejich použití při detekci a analýze malware. První část je věnována malware, jeho historii a jednotlivým typům. Dále je popsán tzv. botnet. Poslední část je věnována samotnému honeypotu a jeho rozdělení. Praktická realizace je uskutečněna přes honeypot Cowrie a Mailoney.

This bachelor thesis is focused on deploying a honeypot to fight malware. The aim was to study the issue of honeypots and their use in detection and analysis of malware. The first part is dedicated to malware, its history and individual types. The so-called botnet is described in the next part. The last part is devoted on the honeypot itself and its distribution. The practical realization is done through honeypots Cowrie and Mailoney.
Honeypot: a tool for fighting malware
Keywords: malware; bezpečnost; honeypot; detekce útoků; detekce zranitelností; malware; security; honeypot; detection of attacks; detection of vulnerabilities